Effects of temperature on the chemical composition of tars produced from the gasification of coconut and palm kernel shells using downdraft fixed-bed reactor - Zubair Yahaya, A. (Elsevier Ltd, 2020)
Tar is derived from the gasification of cellulose and hemicellulose-rich coconut shell (CS) and lignin rich-palm kernel shell (PKS) using a downdraft fixed-bed reactor at 700 Â°Câ900 Â°C. The tar yields and higher heating values from both biomass decrease with the increase in temperature, but high tar yields and higher heating values are obtained from PKS. Fourier transform infrared showed a similar pattern between the wavenumbers of 1500 cmâ1 and 4000 cmâ1, thereby indicating that the main chemical groups in CS and PKS tars are similar. The ultravioletâvisible spectroscopy shows that the aromatic content of tars increases with the increase in temperature, and CS tars show higher fluorescence intensity than PKS tars at >800 Â°C. Proton nuclear magnetic resonance shows that the tars from CS and PKS exhibit highly aromatic and phenolic protons, respectively. Gas chromatographyâmass spectrometry results reveal that the total relative content of compounds in PKS tars is slightly higher than that in CS tars, and phenol group is the most abundant compound at all temperatures. Overall, the formation of aromatics and light PAHs are higher with CS tars, but PKS tars are more stable for the formation of heterocyclic and heavy PAHs. Â© 2019 Elsevier Ltd